The meaning of exception in Hegel´s Philosophy of Right (Revista Eletrônica Estudos Hegelianos, 2020)
The terminological meaning of exception (Ausnahme) has not got much attention either in Hegel’s Philosophy of Rightor in his Science of Logiceven though it has a constitutive function in these texts. To prove this, I will show, first, how Hegel uses the Science of Logicas a presupposition for the Philosophy of Right. Second, I will point out some systematical difficulties related thereto. Our focus lies on his Philosophy of Rightbut in order to ensure a better understanding of our subjet-matter, I will show that the logical term ‘exception’ has a constitutive function within the Logic. Afterwards I describe briefly the structure of the Philosophy of Right, so I can propose an answer to the following questions: In what way is it possible to speak of an “exception” considering the different levels of this work? And in what way is the “exception” constitutive of it?